Genital Ulcer of Behçet Disease Localized in the Vagina May Lack Pain, Making It Difficult to Assess - Soichiro Obata; Koji Kobayashi; Misaki Toda; Etsuko Miyagi; Shigeru Aoki (Case Reports in Rheumatology)
Genital ulcer is one of the main clinical symptoms of Behçet disease; ulcers mostly occur in the vulva and are usually quite painful. We present an unusual case of Behçet disease wherein a painless genital ulcer was localized in the vagina. Our case is of a 43-year-old woman diagnosed with Behçet disease that was controlled with prednisolone. She became pregnant and developed fever, oral ulcers, and arthralgia at 16 weeks of gestation. Although a relapse of Behçet disease was suspected, ulceration and pain of the vulva were not observed. At 18 and 28 weeks of gestation, a vaginal ulcer was observed during regular prenatal examination, but the patient had no pain or other symptoms in the vulva. The vaginal ulcer healed at 29 weeks of gestation. No recurrence of the vaginal ulcer and other symptoms of Behçet disease were seen on subsequent follow-up examination at 1 month after delivery. Although genital ulcers of Behçet disease are common in the vulva and are generally painful, if they are located in the vagina, they can be painless. If Behçet disease is suspected based on other symptoms, a vaginal examination should be conducted as necessary for accurate evaluation of Behçet disease.